A Prosthetic Solution to Poorly Placed Implants in the Posterior Mandible - Michele Albino de Oliveira Treml; Laerte Balduíno Schenkel; Guenther Schuldt Filho (Hindawi Limited, 2018)
The objective of the present study is to find a solution for patients who have multiple implants that are poorly placed in the posterior mandible and require a solution to be rehabilitated, taking into account some diagnostic principles such as maintenance of the occlusal plane, maintenance of correct dental arch inclination, and adequate vertical dimension.